Polymer materials for constructing therapeutical nanoparticles in photothermal therapy - Li, Rui‐Lin; Liu, Chuan‐Jun; Zhang, Xian‐Zheng (Journal of polymer science (2020), 2024)
Photothermal therapy (PTT) ablates tumors by thermal effects of photothermal agents (PTAs), and attracts wide attention due to the non‐invasive characteristic. The ideal PTAs are expected to have high photothermal conversion effect under NIR irradiation, as well as targeting abilities and good biocompatibility satisfying the need of application in vivo. Nanoparticles (NPs) are commonly used as anti‐tumor materials, and plenty of researches on therapeutical NPs for PTT treatment have been developed. Among various building blocks for photothermal NPs, polymer materials for biomedical applications have great advantages due to their negligible toxicity, flexibility for functional modification, and ability to integrate multiple therapeutic strategies. This review focuses on the polymer materials utilized in photothermal NP designing, including their application as excellent carriers and powerful PTAs with great PTT effects. Furthermore, the synergy therapy based on polymeric nanoplatform for enhancing PTT therapeutic efficiency will be introduced.